Effect of Various Flux Compositions Mixed With Slag on Mechanical Properties of Structural Steel Weld Using Submerged ARC Welding - Gupta, Amit; Sapra, Pawan Kumar; Singla, Naveen; Ram, Gora (Asian Review of Mechanical Engineering, 2013)
Submerged arc welding (SAW) is a process in which welding joint is obtained by heating the metal with an arc set between bare electrode and work piece. Intense heat produced during the process fuses the metal and filler metal. Flux is used as a shielding agent which is placed over the welding area to protect the molten pool from atmospheric contamination. It also shields the spatter of arc. This flux gets converted into slag after solidification at the surface of welding metal. The wastage of flux in the form of slag increases the cost of process. In the present study different flux and slag compositions are used to analyse the effect of slag/flux mixture on mechanical properties of submerged arc welded joint performed on mild steel plates. Present work is an attempt to utilize this slag as flux and reduce the cost of SAW welding process. For the investigation three agglomerated flux compositions are prepared and slag is mixed in these compositions in percentage of 10, 20, and 30 respectively. The various tests such as tensile test, impact test, microhardness test, microstructure test were performed on the welded specimens, to study the mechanical behaviour of structural steel. It is found that the mechanical properties of the welded joint by mixing slag in all three flux compositions are significant according to AWS requirement.